Finite-horizon inverse optimal control for discrete-time nonlinear systems. (January 2018) - Molloy, Timothy L.; Ford, Jason J.; Perez, Tristan
Abstract: In this note, we consider the problem of computing the parameters (or weights) of an optimal control objective function given optimal closed-loop state and control trajectories. We establish a method of inverse optimal control that exploits the discrete-time minimum principle. Under a testable matrix rank condition, our proposed method is guaranteed to recover the unknown objective-function parameters of finite-horizon discrete-time nonlinear optimal control problems.